Raportowanie środowiskowe : teoria i praktyka w świetle doświadczeń międzynarodowych - Brzozowski, Tomasz (Environmental Reporting : the International Experence : Theory and Practice, 2005)
Environmental report is a publicly available document issued volountary by companies. This paper shows recommendations and requirements for environmental reporting process. Practice of publish environmental reports become more and more popular among companies. Some of reports were described and compared.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (3); 2005; nr 1075, s. 49-59